Photobiomodulation for the Treatment of Primary Headache: Systematic Review of Randomized Clinical Trials - Andréa Oliver Gomes; Ana Luiza Cabrera Martimbianco; Aldo Brugnera Junior; Anna Carolina Ratto Tempestini Horliana; Tamiris da Silva; Elaine Marcílio Santos; Yara Dadalti Fragoso; Kristianne Porta Santos Fernandes; Samir Nammour; Sandra Kalil Bussadori (Life, 2022)
The purpose of this study was to evaluate the efficacy and safety of photobiomodulation as an adjuvant treatment for primary headache. A systematic review of randomized clinical trials was performed. For such, electronic searches were performed in the MEDLINE, Embase, Cochrane Library, LILACS, PEDro, PsycInfo, Clinicaltrials.gov., and WHO/ICTRP databases, with no restrictions imposed regarding language or year of publication. We included studies that assessed any photobiomodulation therapy as an adjuvant treatment for primary headache compared to sham treatment, no treatment, or another intervention. The methodological assessment was conducted using the Cochrane Risk of Bias tool. The certainty of the evidence was classified using the GRADE approach. Four randomized clinical trials were included. Most of the included studies had an overall high risk of bias. Compared to sham treatment, photobiomodulation had a clinically important effect on pain in individuals with primary headache. Despite the benefits reported for other outcomes, the estimates were imprecise, and the certainty of the evidence was graded as low. These findings are considered insufficient to support the use of photobiomodulation in the treatment of primary headache. Randomized clinical trials, with higher methodological quality, are needed to enhance the reliability of the estimated effects.